Lima Andina: A digital tool for the history of internal migration in Peru - Durston, Alan (2026)
This note presents a digital platform containing more than six thousand notices published by internal migrant associations in the newspaper El Comercio between 1906 and 1933, allowing for a systematic study of the presence and dynamics of these associations in Lima in the early twentieth century. Based on a database that records 488 organizations and their notices, the platform offers search and visualization tools useful for exploring patterns of migration, sociability, and political participation. The note describes the methodological decisions and collaborative process behind the project, highlighting both the challenges of digital work and its potential for future historicalresearch.